2021
DOI: 10.2217/cer-2021-0109
|View full text |Cite
|
Sign up to set email alerts
|

Real-world treatment, clinical outcomes and healthcare resource utilization among persons with hemophilia A by age

Abstract: Aim: Examine real-world characteristics, treatment patterns, and outcomes among treated persons with hemophilia A (PwHA) stratified by age. Patients & methods: This study utilized US claims data from 1 January 2007–31 July 2018 from the Humana Research Database. Unadjusted comparisons were conducted across PwHA (<18, 18–55, 56–89 years) enrolled in commercial or Medicare Advantage Prescription Drug plans. Results: A total of 294 PwHA were identified; 21.1% experienced ≥1 bleeding event, and 41.2 and 53.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Consistent with former studies, this study suggestedthat prophylaxis therapy decreases the frequency of haemorrhages, which is bene cial to prevent the progression of haemophilic complications [3,9,10,14,17]. Furthermore, we add the new evidence that it also signi cantly relieves chronic pain related to haemophilia [37]. There was no statistical difference in the number of target joints and the probability of disability for children with different treatment regimens.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with former studies, this study suggestedthat prophylaxis therapy decreases the frequency of haemorrhages, which is bene cial to prevent the progression of haemophilic complications [3,9,10,14,17]. Furthermore, we add the new evidence that it also signi cantly relieves chronic pain related to haemophilia [37]. There was no statistical difference in the number of target joints and the probability of disability for children with different treatment regimens.…”
Section: Discussionsupporting
confidence: 88%
“…Consistent with former studies, this study suggested that prophylaxis therapy decreases the frequency of hemorrhages, which is beneficial to prevent the progression of hemophilic complications [ 3 , 9 , 10 , 14 , 17 ]. Furthermore, we add new evidence that it also significantly relieves chronic pain related to hemophilia [ 37 ]. There was no statistical difference in the number of target joints and the probability of disability for children with different treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18] Currently, real-world studies of prophylactic FVIII use in hemophilia A are limited. 7,[19][20][21] HEM-POWR is an ongoing, Phase 4, observational, 36-month study assessing the effectiveness and safety of damoctocog alfa pegol in real-world PTPs. 22 The first interim analysis of the HEM-POWR real-world study showed that the recombinant FVIII prevented bleeding and was well tolerated, with no study drug-related adverse events (AEs) in a small group of patients.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, real‐world studies of prophylactic FVIII use in hemophilia A are limited 7,19–21 . HEM‐POWR is an ongoing, Phase 4, observational, 36‐month study assessing the effectiveness and safety of damoctocog alfa pegol in real‐world PTPs 22 .…”
Section: Introductionmentioning
confidence: 99%